Risk of tuberculosis transmission by children to healthcare workers - a comprehensive review - Diel, Roland; Nienhaus, Albert (German Medical Science GMS Publishing House, 2023)
Background: Healthcare workers (HCWs) are at increased risk of becoming infected with complex (Mtbc). Objective: To assess the magnitude of Mtbc transmission by children under the age of 15 years to HCW. Methods: Medline, Google Scholar and Cochrane library were searched to select primary studies in which a child was the presumed index case and exposed HCW were screened for latent TB infection (LTBI).Results: Of 4,702 abstracts, 15 original case reports covering 16 children with TB were identified. In sum, 1,395 HCW were contact persons and underwent testing. Ten of the studies reported TST conversion, amounting to 35 (2.9%) of the 1,228 HCW tested. In three of the TST-based and both of the studies that used IGRA testing, conversion was absent. 12 of the 15 studies (80%) reported exposure of HCW in neonatal intensive units (NICUs) to premature infants suffering from congenital pulmonary TB. One study including two infants addressed possible pulmonary Mtbc transmission in a general pediatric ward. Extrapulmonary transmission by aerosolized Mtbc was suggested in two patients, an infant with tuberculous peritonitis and a 12-year-old adolescent with pleurisy, and culture-confirmed only after the child had undergone video-assisted thoracoscopic surgery. Routine use of protective facemasks by HCW before exposure was not mentioned in any of the included studies. Conclusions: The results suggest that the risk of Mtbc transmission from children to HCW is low. Particular attention should be paid to infection risk during respiratory manipulations in NICUs. The consistent wearing of facemasks may further reduce the risk of Mtbc transmission.